2022
DOI: 10.1002/adfm.202210939
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Ru, O Co‐Doping MoS2 for Hydrogen Evolution Reaction Electrocatalyst and Surface‐Enhanced Raman Scattering Substrate: High‐Performance, Recyclable, and Durability Improvement

Abstract: Molybdenum disulfide (MoS 2 ) is a promising non-precious material for hydrogen evolution reaction (HER) electrocatalysts and surface-enhanced Raman scattering (SERS) substrates. However, its inert basal plane, poor active sites, and limited stability hamper their commercial prospects. Herein, Ru, O co-doped MoS 2 (MSOR x ) for accelerating the charge transfer and building more active sites using one-step hydrothermal method is designed to address these obstacles. The outstanding HER performances of the MSOR 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 58 publications
1
14
0
Order By: Relevance
“…Element doping is another promising method to optimize the SERS performance of semiconductor substrates by energy band engineering. 148–152 Yang et al found that Mo-doped Ta 2 O 5 substrate could exhibit a remarkable SERS sensitivity with an EF of 2.2 × 10 7 and a low LOD 9 × 10 −9 M for methyl violet (MV) molecules under the 532 nm laser excitation (Fig. 4B).…”
Section: Single-component Sers-active Nanomaterialsmentioning
confidence: 99%
“…Element doping is another promising method to optimize the SERS performance of semiconductor substrates by energy band engineering. 148–152 Yang et al found that Mo-doped Ta 2 O 5 substrate could exhibit a remarkable SERS sensitivity with an EF of 2.2 × 10 7 and a low LOD 9 × 10 −9 M for methyl violet (MV) molecules under the 532 nm laser excitation (Fig. 4B).…”
Section: Single-component Sers-active Nanomaterialsmentioning
confidence: 99%
“…77 This strategy could create abundant catalytic centers and electron transfer effect from the Ni 2 P phase to the (Fe, Ni) 2 P phase, as Enormous works have proved that heteroatom doping can regulate the electronic properties of materials which could improve the HER performance. [80][81][82][83] Therefore, several groups introduced integrated strategies of doping and heterostructure construction. To illustrate, Yuan et al used sulfur for doping the core-shell architecture of Co 2 P@Ni 2 P to promote hydrogen production, as shown in Fig.…”
Section: Synthesis Of Nickel Phosphidesmentioning
confidence: 99%
“…For example, Gao et al reported that the O incorporated into Ru 1 /MoS 2 (O-Ru 1 /MoS 2 ) was successfully prepared by one-pot hydrothermal method. [155] Due to the incorporated O atoms, the electron density of Ru atom in MoS 2 could be well tuned, subsequently generating the highly catalytic sites for HER. As a result, the O-Ru 1 /MoS 2 was shown to exhibit superior HER activities in full pH media.…”
Section: Metal Sulfidesmentioning
confidence: 99%